Effects of build orientation and heat treatment on the evolution of microstructure and mechanical properties of alloy Mar-M-509 fabricated via laser powder bed fusion. (October 2019) - Ferreri, Nicholas C.; Ghorbanpour, Saeede; Bhowmik, Shubhrodev; Lussier, Ryan; Bicknell, Jonathan; Patterson, Brian M.; Knezevic, Marko
Abstract: This paper describes the main results from an experimental investigation into the consequences of various microstructural features, created by laser powder bed fusion (LPBF) and subsequent heat treatments (HTs), in alloy Mar-M-509 on several aspects of plastic deformation including mechanical anisotropy and elongation-to-fracture (ETF). To ensure successful manufacturing of the alloy, porosity fraction and distribution are first characterized using micro X-ray computed tomography. Next, grain structure, crystallographic texture, and regions of recrystallization in the studied microstructures are measured using electron backscattered diffraction (EBSD). Finally, chemistry, distribution, and morphological features of carbide phases are extracted using electron microscopy and X-ray diffraction. Strength in tension and compression are measured at room temperature for different initial microstructures created by variations in manufacturing conditions and sample orientations with respect to sample processing frame. While the strength of the alloy varies with sample orientation by approximately 30% in the as-built condition, the alloy is softer, more ductile, and approximately isotropic after HT. These results are discussed and critically compared with the data reported for the as-cast material. The alloy manufactured via LPBF is found to be significantly stronger and more ductile than the same alloy produced by casting. The interesting deformation behavior characteristics of the samples in different conditions are explained in terms of their microstructures. EBSD measurements reveal evolution from columnar grains along the build direction favoring a moderately strong <001> fiber texture in the as-built material to equiaxed grains favoring the { 110 } <001> Goss texture component after subsequent HTs. The major change in grain structure and texture is a result of recrystallization. While carbide phases precipitate primarily at dendrite and cellular interfaces in the as-built material, these phases are both intra-and inter-granular within the HT materials and coarsen with HT duration. These microstructural observations formed bases to rationalize the observed mechanical behavior of the alloy. In closing, tailoring the alloy performance characteristics with HTs is discussed. Highlights: Mar-M-509 superalloy fabricated via AM is significantly stronger and more ductile than the same alloy produced by casting. Role of microstructures, created by AM, on elongation-to-fracture, strength, and anisotropy of the alloy is elucidated. Anisotropy in the as-built material is caused by directional grain and cellular dendritic structures coupled with texture. Dispersed carbides induce a Zener drag effect on grain boundaries promoting growth of Goss texture during recrystallization. Heat treatment time reduces strength of the alloy owing to dendrite dissolution and reduced carbide dispersion strengthening.